Advanced analytics and AI : impact, implementation, and the future of work - Boobier, Tony, 1956- (Wiley finance series., 2018)
Introduction; Construction; Augmented Reality; Drones and Remote Imagery; Contractor Plant and Equipment; Employee Behaviour; Cultural Change in Construction; Utilities and Infrastructure Resilience; Construction Industry Summary; Utilities; Electrical Power; Gas; Water; Wastewater; Smart Homes, Smart Infrastructure?; Interconnectivity, Poverty, and Famine; Public Services; Education; Policing; Healthcare; Agriculture; Technology Industry; Conclusion; Notes; Chapter 5: The Impact of AI on Professions; Summary; Introduction; Work and Professions; The Importance of Competences.